Factors Associated with Patient-Reported Penile Length Loss After Radical Cystoprostatectomy in Male Patients with Bladder Cancer. Issue 5 (29th February 2020) - Loh-Doyle, Jeffrey C.; Han, Jullet; Ghodoussipour, Saum
Abstract: Background: The perception of penile length loss is common in male patients undergoing radical prostatectomy; however, this has not been described after radical cystoprostatectomy (RC). Aim: To evaluate perceptions of penile length loss in male patients after RC and contributing factors. Methods: Patients completed an institutional review board–approved questionnaire comprised the International Index of Erectile Function (IIEF-5) and supplemental questions including perceived changes in penile length after RC. Multivariable analysis was performed to determine associations between the perception of penile length loss and the amount of length lost with patient and surgery-specific factors. Outcomes: The rate of patient-reported penile length loss and factors contributing to this perception was the outcome of this study. Results: From October 2017 to January 2019, 151 patients completed the questionnaire. The median age at cystectomy was 66.1 years (interquartile range [IQR]: 59.4–73.3), and the median duration of follow-up was 28.3 months (IQR: 13–74.1). Preoperative IIEF-5 was available in 55 patients with a median score of 14 (IQR: 3–20). The median IIEF-5 score at time of survey completion was 3 (IQR: 1–18). The majority of patients (55.1%) reported a perceived loss of penile length, 20.4% reported no loss, and 24.5% were unsure. Of those who quantified their loss in penile length, 54.6% reported losses of an inch or more. Neurovascular preservation was not found to protect against penile length loss but did correlate with a reduction in the amount reported lost ( P = .008). Multivariable logistic regression analysis identified increasing IIEF-5 score at time of survey completion to protect against a perceived loss in penile length (odds ratio: 0.924, 95% confidence interval: 0.878–0.973, P = .0025), whereas increasing body mass index was associated with a loss in perceived penile length (odds ratio: 1.198, 95% confidence interval: 10.53–1.383, P = .0060). Clinical Implications: The perception of penile length loss is a commonly held belief in patients after RC, and many patients will perceive losses that exceed 1 inch (2.54 cm). Strengths and Limitations: This study is the first series to describe the perception of penile length loss after RC. It is strengthened by the study population's size, heterogeneity, and patient-reported results. It is limited by lack of objective measurements of stretched penile length. Conclusions: RC can result in significant sexual dysfunction including the perceived loss of penile length.